SUSTAINABILITY'S INFLUENCE ON ENERGY FIRM PERFORMANCE: AN ESG PERSPECTIVE - Puteri Utami; Imo Gandakusuma (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2023)
Growing concerns about climate change have gained prominence in the business landscape, leading to various studies with varied findings. Some researchers argue that companies prioritizing ESG considerations tend to outperform their peers financially. However, the literature focused on the oil and gas sector has produced conflicting results when attempting to establish a connection between corporate social responsibility and firm efficiency. This study aims to thoroughly investigate the correlation between ESG implementation and the performance of energy firms between 2017 and 2021. ESG scores and ESG Pillars were employed as proxies for evaluating ESG performance across 79 energy companies. The results of this study indicate that the implementation of ESG does not have a positive and significant impact on ROA and ROE of energy companies but can have a positive and significant impact on the market performance of energy companies (SMR), especially in developed countries. The results of this study also show that investors prioritize active environmental engagement and effective governance policies when making investment decisions in the energy sector